The Analysis of Code Switching in Indonesian Popular Pop Songs in 2000's - 2010's - Rin Rin Rinawati (Universitas Pendidikan Ganesha, 2021)
Songs can be a media to uses code switching, and there are a lot of this kind of songs in Indonesia. So to help in better understanding of code switching, the analysis of code switching and in Indonesian song must be done. The objective of this research was to describe the type of code switching that were found in some Indonesian popular pop songs from 2000’s – 2010’s and to explain the cause of code switching in Indonesian popular pop songs from 2000’s – 2010’s. The research used content analysis design. The main research instrument was the researcher herself. The object of the data was the song lyric of seven songs that represented pop songs in 2000's - 2010's. To collect the data, the researcher used content analysis technique. Based on the analysis there were 32 data of types of code switching and its causes. There are three types of code switching based on poplack’s theory that are found. The first types of code switching that were found was tag switching with one data. Second, inter-sentential switching with 26 data which is the types of code switching that is commonly found. The last is intra-sentential switching with 5 data. The cause of code switching found were 5 out of 7 causes of code switching based on hoffman’s theory with the most commonly found was talking about particular topic with 23 data. Quoting somebody else with 2 data, interjection only 1 data, repetition used for clarification with 2 data, and the last was intention of clarifying the speech content for interlocutor with 4 data. Since this research only investigate the types of code switching and the causes based on relevant theories. Therefore, the researcher suggests for other researcher who interested in this topic to also analyze code mixing or the impact of using code switching for listener. Keywords : Code Switching, The cause of code switching